Peran Pengelolaan Piutang, Diskon Pembayaran Dini, dan Suku Bunga dalam Menentukan Kebijakan Kredit Perusahaan - Annisa Trimur Fadila; Eva Elysa Putri; Ziyadatul Khoiroh; Febriyanti Artika Putri; Maria Yovita R. Pandin (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
In a dynamic and competitive business environment, companies are required to manage financial aspects effectively, especially in determining credit policies. This study aims to analyze the role of receivables management, early payment discounts, and interest rates in determining the company's credit policy. The method used is a qualitative approach with a literature study based on secondary data, including receivables data from five large financial companies in Indonesia and Bank Indonesia's benchmark interest rate during 2022 to 2024. The results of the study show that despite a significant increase in interest rates, all companies were still able to increase the value of their receivables. Strategies such as providing early payment discounts have proven effective in accelerating cash flow and maintaining the quality of receivables.